О некоторых вопросах зарождения и деятельности политических партии Казахстана конца ХIХ и нач. XX-го века = O nekotorykh voprosakh zarozhdeniya i deyatel'nosti politicheskikh partii Kazakhstana kontsa XIX i nach. XX-go veka - НУРПЕИСОВА, Бахыт (Historia i Świat, 2021)
The article highlights the history of the origin and activities of various political parties in Kazakhstan that came to the political arena in the late 19th and early 20th centuries. On the basis of archival documents and other sources, the program provisions, goals and objectives of their activities have been studied. The article describes and analyzes the composition of the participants in political parties and movement. The forms, methods of struggle are described, the reasons and conditions for the emergence of political parties and movements that existed at that time are analyzed. Also important in the political life of Kazakhstan at the beginning of the twentieth century, the history of the origin and activities of the national party ‘Alash’. The article devotes a special place to political exiles who deserve an assessment of their tireless activity, who, despite the strict and secret surveillance of the gendarmerie, continued the struggle against the tsarist autocracy. The political exiles of the beginning of the 20th century, who found themselves in a foreign land in captivity and cut off from their own living environment, already in the new conditions are organized into political unions and continue to fight